You’ve Opened Your Doors: What’s Next? : Digital Lending During and After the Pandemic - Myers, Carla S.; Benson, Sara; Vollmer, Timothy (Journal of Copyright in Education & Librarianship, 2022)
During the heart of the COVID-19 pandemic, when nearly all lending of books and physical materials in the collections of college and research libraries was impossible due to campus closures, many HathiTrust member libraries participated in the Emergency Temporary Access Service (ETAS). This program permitted patrons of eligible libraries to access—in a limited fashion—a digitized HathiTrust book that corresponded to a physical book held in the collection of the member library. Although the ETAS was closed down after libraries reopened their doors, many libraries are exploring similar “controlled digital lending” services that leverage limitations and exceptions to copyright to support digital access options for patrons.